Psychological Resilience in Military Personnel: The Role of Spirituality and Self-Efficacy - Auliansyah, Mutia; Hidayat, Ahmad; Sari, Wina Diana (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2026)
Military personnel are expected to demonstrate strong psychological resilience in order to cope with demanding duties, operational pressure, and high-risk working conditions. Resilience allows individuals to adapt effectively, recover from adversity, and maintain stable performance under stressful circumstances. Nevertheless, studies investigating the contribution of spirituality and self-efficacy to resilience among Indonesian military personnel are still relatively scarce. This research aimed to examine how spirituality and self-efficacy influence resilience of Indonesian Air Force personnel serving at Roesmin Nurjadin Air Base, Pekanbaru. A quantitative correlation method utilizing structural equation modeling with partial least squares (SEM-PLS) was employed. The study included 210 military personnel participants selected through convenience sampling. Data were collecting using questionnaires measuring spirituality, self-efficacy, and resilience. The findings indicated that both spirituality and self-efficacy significantly contributed to resilience, with self-efficacy showing a greater predictive influence. Furthermore, the two variables, namely spirituality and self-efficacy, jointly accounted for 43% of the variance in resilience. These results suggest that strengthening spiritual values and personal confidence may help improve psychological endurance and readiness among military personnel facing challenging operational responsibilities.